Immigrant Supply of Marketable Child Care and Native Fertility in Italy - R. D. Mariani; F. C. Rosati (Global Labor Organization (GLO), 2021)
The availability of child-care services has often been advocated as one of the instruments to counter the fertility decline observed in many high-income countries. In the recent past large inflows of lowskilled migrants have substantially increased the supply of child-care services. In this paper we examine if the flow of immigrants as actually affected fertility exploiting the natural experiment occurred in Italy in 2007, when a large inflow of migrants - many of them specialized in the supply of child care - arrived unexpectedly. With a difference-in-differences method, we show that newly arrived immigrant female workers have increased the number of native births by roughly 2 per cent. We validate our result by the implementation of an instrumental variable approach and several robustness tests, all concluding that the increase in the supply of child-care services by immigrants has positively affected native fertility choice.
Keywords: D12; F22; J13; J61; 330; Household Economics; Fertility; Immigrant Labour; International Migration